Asthma, chronic bronchitis, and exposure to irritant agents in occupational domestic cleaning: a nested case-control study. Issue 9 (18th August 2005) - Medina-Ramón, M; Zock, J P; Kogevinas, M; Sunyer, J; Torralba, Y; Borrell, A; Burgos, F; Antó, J M
Abstract : Background: Women employed in domestic cleaning are at increased risk for symptoms of obstructive lung disease, but the agents responsible are unknown. Aims: To investigate common tasks and products in occupational domestic cleaning in relation to respiratory morbidity. Methods: Case-control study in domestic cleaning women nested within a large population based survey of women aged 30–65 years; 160 domestic cleaning women with asthma symptoms, chronic bronchitis symptoms, or both and 386 without a history of respiratory symptoms were identified. Detailed exposures were evaluated for 40 cases who reported still having symptoms at the recruitment interview, and 155 controls who reported not having symptoms. All tasks performed and products used when cleaning houses were determined in a face-to-face interview. Lung function, methacholine challenge, and serum IgE testing were performed. Personal exposure measurements of airborne chlorine and ammonia were performed in a subsample. Associations between asthma, chronic bronchitis, and cleaning exposures were evaluated using multiple logistic regression analysis. Results: Airborne chlorine (median level 0–0.4 ppm) and ammonia (0.6–6.4 ppm) were detectable during occupational domestic cleaning activities. Cases used bleach more frequently than controls; adjusted odds ratio (OR) for intermediate exposure was 3.3 (95% CI 0.9 to 11) and for high exposure 4.9 (1.5 to 15). Other independent associations included accidental inhalation of vapours and gases from cleaning agents and washing dishes. These associations were more pronounced for cases with asthma symptoms than for those with symptoms of chronic bronchitis, but were not related to sensitisation to common allergens. Conclusions: Asthma symptoms in domestic cleaning women are associated with exposure to bleach and possibly other irritant agents. The public health impact of the use of irritant cleaning products could be widespread since the use of these products is common both in the workplace and at home.